Quasistatic effective parameters of vibrating elements of electro-acoustic transducers - DOBRUCKI, Andrzej B.; SZMAL, Cecylia (Archives of Acoustics, 1988)
This paper presents an approximate theory of determining effective parameters determining of surface elements of electro-acoustic transducers. It considers the distribution of displacements of these elements due to a steady load. Furthermore, a critical analysis of existing definitions of active surface was carried out and a new definition was proposed. It is a generalization of hitherto applied definitions. Equivalence of these definitions was proved. Examples of effective parameters calculations for systems with known accurate solutions are given. High consistency of proposed approximate methods with these solutions was demonstrated. Moreover examples of calculations of quasistatic effective parameters of systems previously solved with approximate methods are given.